Ethical Aspects of Social Research: Old Concerns in the Face of New Challenges and Paradoxes. A Reflection from the Field of Biographical Method - Kaźmierska, Kaja (Qualitative Sociology Review, 2020)
The paper deals with the ethical aspects of the research process and contemporary changes in this field, which make the discussion on ethical dilemmas and concerns more dynamic and varied. Although in natural science and social sciences one can find a common ground related to the most general ethical principles. In the article I refer primarily to the social sciences. The article discusses three aspects affecting the dynamics of ethical discussions: the development of research in the field of natural sciences leading to many ethical dilemmas and forcing ethical codification of research proceedings also in the area of social sciences; the increase in sensitivity and social consciousness and not only awareness of research as such (processes of democratization, emphasizing human and animal rights, protection of minority rights, the process of individualization); the dynamics of contemporary social changes resulting from the development of technology, especially the Internet, which has become a global resource of data and their exchange. This forces qualitative researchers to consider the issue of data archiving, their reanalysis, and determining the boundary for creating Big Qualidata from them. The article discusses these three dimensions, with particular emphasis on the last of them, which will be commented on in relation to the specific methodological approach, which is biographical research.